2001
DOI: 10.2307/3871528
|View full text |Cite
|
Sign up to set email alerts
|

Tomato SP-Interacting Proteins Define a Conserved Signaling System That Regulates Shoot Architecture and Flowering

Abstract: Divergent architecture of shoot models in flowering plants reflects the pattern of production of vegetative and reproductive organs from the apical meristem. The SELF-PRUNING (SP) gene of tomato is a member of a novel CETS family of regulatory genes (CEN, TFL1, and FT) that controls this process. We have identified and describe here several proteins that interact with SP (SIPs) and with its homologs from other species: a NIMA-like kinase (SPAK), a bZIP factor, a novel 10-kD protein, and 14-3-3 isoforms. SPAK, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
98
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 55 publications
(92 reference statements)
4
98
0
2
Order By: Relevance
“…6). 5F) and was reported to be a mobile signal that mediates the transition to flowering (41,42). CLV proteins are responsible for controlling the size of the SAM; they restrict the population of stem cells by limiting the expression of the transcription factor WUSCHEL (WUS) in the peripheral zone of the meristem (36,43,44).…”
Section: Resultsmentioning
confidence: 99%
“…6). 5F) and was reported to be a mobile signal that mediates the transition to flowering (41,42). CLV proteins are responsible for controlling the size of the SAM; they restrict the population of stem cells by limiting the expression of the transcription factor WUSCHEL (WUS) in the peripheral zone of the meristem (36,43,44).…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of other cell cycle-related proteins has also been shown to affect the morphology of floral organs, including the ectopic expression of ICK1, a CDK inhibitor in Arabidopsis, which showed drastic growth and cell division inhibition [39]. As well, both the antisense expression of the tomato SPAK and the ectopic expression of its C-terminal extension resulted in the formation of pear-shaped fruits [10].…”
Section: Discussionmentioning
confidence: 99%
“…AmnimA was recovered as a partial 500 bp fragment in the catalytic kinase domain [9]. SPAK was shown to interact with SP, a 23-kDa protein involved in shoot architecture and flowering regulation [10]. SPAK was also found to interact with 14-3-3 isoforms and self-pruning interacting protein 4 (SIP4) a novel 10 kDa protein.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, induction of TFL1 results in a suppression of flowering (6,7,17,18). Genetic analyses show that TFL1 and FT act independently in flowering control but, so far, studies in different plant species have not revealed the biochemical mechanism of this family of proteins (8,9,11,(13)(14)(15)(22)(23)(24).TFL1 and FT are homologous to phosphatidylethanolaminebinding proteins (PEBPs), a wider group of proteins that have diverse roles in animals, yeast, and bacteria. The PEBP family regulates signaling pathways to control growth and differentiation.…”
mentioning
confidence: 99%